Three Randomised Phase I/IIa Trials of 5% Cis-urocanic Acid Emulsion Cream in Healthy Adult Subjects and in Patients with Atopic Dermatitis - Juha M. Peltonen; Liisa Pylkkänen; Christer T. Jansén; Iina Volanen; Terhi Lehtinen; Jarmo K. Laihia; Lasse Leino (Society for the Publication of Acta Dermato - Venereologica, 2022)
New treatment modalities are needed in atopic dermatitis. We evaluated the pharmacokinetics, safety, tolerability, and efficacy of topical cis-urocanic acid (cis-UCA) cream in randomised vehicle-controlled double-blinded clinical trials. The subjects received 5% cis-UCA emulsion cream and control vehicle on volar forearms after right–left randomisation. Study 1: 16 healthy subjects received one dose on the skin and, a week later, on DMSO-irritated skin. Study 2: 16 healthy subjects received 2 daily doses for 10 days. Study 3: 13 patients with mild to moderate disease were treated on selected skin lesions twice daily for 28 days. Study treatments were well tolerated. cis-UCA remained close to endogenous levels in plasma and urine. cis-UCA reduced transepidermal water loss (TEWL) both in healthy subjects and in the patients. Eczema area severity index and physician’s global assessment improved from baseline with both treatments. cis-UCA cream improved skin barrier function and suppressed inflammation in the human skin.